When it’s not a complicated frontal sinusitis - A Langerhans Cell Histiocytosis case-report - Henrique Teixeira; Mariana Branco Lopes; Ricardo São Pedro; Maria Helena Rosa; Luís Antunes (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Langerhans cell histiocytosis (LCH) is a rare and heterogeneous disease that appears mainly in children and frequently affects bone structures such as the skull, with possible involvement of the orbit. In this paper, we present the case of an 11-year-old boy who came to the emergency department with left periorbital edema and erythema with about 10 days of progressive worsening. Computed tomography was compatible with complicated left frontal sinusitis with bone erosion into the orbit and intracranial compartment, and magnetic resonance imaging corroborated these findings. Due to the lack of improvement with medical therapy, surgical exploration was performed through an external approach, identifying a lesion in which the anatomopathological study confirmed the diagnosis of LCH.